Cysteine Mutations in the Ebolavirus Matrix Protein VP40 Promote Phosphatidylserine Binding by Increasing the Flexibility of a Lipid-Binding Loop - Kristen A. Johnson; Nisha Bhattarai; Melissa R. Budicini; Carolyn M. LaBonia; Sarah Catherine B. Baker; Bernard S. Gerstman; Prem P. Chapagain; Robert V. Stahelin (Viruses, 2021)
Ebolavirus (EBOV) is a negative-sense RNA virus that causes severe hemorrhagic fever in humans. The matrix protein VP40 facilitates viral budding by binding to lipids in the host cell plasma membrane and driving the formation of filamentous, pleomorphic virus particles. The C-terminal domain of VP40 contains two highly-conserved cysteine residues at positions 311 and 314, but their role in the viral life cycle is unknown. We therefore investigated the properties of VP40 mutants in which the conserved cysteine residues were replaced with alanine. The C311A mutation significantly increased the affinity of VP40 for membranes containing phosphatidylserine (PS), resulting in the assembly of longer virus-like particles (VLPs) compared to wild-type VP40. The C314A mutation also increased the affinity of VP40 for membranes containing PS, albeit to a lesser degree than C311A. The double mutant behaved in a similar manner to the individual mutants. Computer modeling revealed that both cysteine residues restrain a loop segment containing lysine residues that interact with the plasma membrane, but Cys311 has the dominant role. Accordingly, the C311A mutation increases the flexibility of this membrane-binding loop, changes the profile of hydrogen bonding within VP40 and therefore binds to PS with greater affinity. This is the first evidence that mutations in VP40 can increase its affinity for biological membranes and modify the length of Ebola VLPs. The Cys311 and Cys314 residues therefore play an important role in dynamic interactions at the plasma membrane by modulating the ability of VP40 to bind PS.